Phase evolution of Cu2ZnSnS4 (CZTS) nanoparticles from in situ formed binary sulphides under solvothermal conditions. Issue 45 (20th May 2021) - Ahmad, Rameez; Saddiqi, Naeem-ul-Hasan; Wu, Mingjian; Prato, Mirko; Spiecker, Erdmann; Peukert, Wolfgang; Distaso, Monica
Abstract : Cu2 ZnSnS4 (CZTS) nanocrystals form both by direct nucleation and growth and by conversion of binary sulphides into the quaternary phase via internal recrystallization processes. Abstract : Cu2 ZnSn(S, Se)4 (CZTSSe) are benign and low-cost materials, overcoming the limitations of toxicity and high costs of other semiconductors such as CuInGa(S, Se)2, cadmium and lead chalcogenides, and Pb-based perovskites widely used in photovoltaic and thermoelectric applications. In order to shed light on the formation mechanism of CZTS nanoparticles using anisole as the solvent, oleylamine as the organic ligand, carbon disulphide as the sulphur source and Zn(NO3 )2 ·6H2 O as the Zn(ii ) precursor, we follow the conversion of binary sulphides formed in situ under solvothermal conditions into quaternary phases. Besides a careful microstructural characterization of the as-synthesized materials by X-ray diffraction (XRD), Raman spectroscopy, electron microscopy (TEM and HRTEM) and energy dispersive X-ray (EDX) spectroscopy at micron- and nano-scale, we study the evolution of particle surface properties by X-ray-photoelectron spectroscopy (XPS). The results show that CZTS particles form already during the early stages of the reaction, most probably through a nucleation and growth mechanism. In parallel, a comparably slower growth mechanism is observed that involves recrystallization between the binary phases, without evidence of ternary phase formation.